Unraveling chromosomal and genotoxic damage in individuals occupationally exposed to coal from underground mining - Buitrago-Rodríguez, María Yolanda; Rangel, Nelson; Vega-Valderrama, Juan D.; Pulido-Medellín, Martín; Rondón-Lagos, Milena (Frontiers in Genetics, 2024)
Purpose: Coal mining is a vital sector in Colombia, contributing significantly to the nation's economy and the development of its regions. However, despite its importance, it has led to a gradual decline in the health of mine workers and nearby residents. While the adverse health effects of open-pit coal mining on exposed individuals have been well-documented in Colombia and globally, studies investigating genetic damage in underground coal miners are lacking. Methods: The aim of our study was to evaluate chromosomal and genotoxic damage, in peripheral blood samples from a group of underground coal miners and residents of areas exposed to coal, in the town of Samacá, Boyacá-Colombia, and in a group of unexposed individuals by using banding and molecular cytogenetic techniques, as well as cytokinesis block micronucleus assays.Results: Our results suggest that occupational exposure to coal induces chromosomal and genotoxic damage in somatic cells of underground coal miners. Chromosomal and genotoxic damage is an important step in carcinogenesis and the development of many other diseases. Our findings provide valuable insights into the effects of coal dust exposure on chromosomal integrity and genetic stability.Conclusions: Our pilot study suggests that occupational exposure to coal induces chromosomal damage in underground coal miners, highlighting the importance of validating these findings with a larger sample size. Our results highlight the need to implement prevention and protection measures, as well as educational programs for underground coal miners. Characterizing and estimating exposure risks are extremely important for the safety of people exposed occupationally and environmentally to coal and its derivatives.